Valsalva-Induced Spontaneous Suprachoroidal Hemorrhage: A Case Report and Review of the Literature - Bijon, Jacques; Schalenbourg, Ann (Klinische Monatsblätter für Augenheilkunde, 2022)
We report a rare case of spontaneous suprachoroidal hemorrhage and present a systematic review of the literature using PubMed/Medline databases. Patients that developed a spontaneous suprachoroidal hemorrhage with a history of previous intraocular surgery were excluded. An 82-year-old male patient with no known ocular pathologies or surgical history was referred with acute ocular pain and decreased vision in the right eye (BCVA: 0.6 with hyperopic correction) following a Valsalva maneuver. General history included chronic heart failure and coronary artery disease, treated with anticoagulant and antihypertensive drugs. Dilated fundus examination revealed a posterior red-brown choroidal mass, with a thickness of 1.5 mm on B-scan ultrasonography. The lesion was not visible on fluorescein or indocyanine green angiography and was located under the choroid on B-scan optical coherence tomography. The diagnosis of a spontaneous suprachoroidal hemorrhage was evoked, and the patient was observed. Five months later, BCVA was 1.0 uncorrected, with a normal-appearing fundus. In a literature review, eight cases of spontaneous suprachoroidal hemorrhage following an episode of increased intrathoracic pressure were identified, including our patient. M/F ratio was 1 : 1, with a median age of 66.5 years. All cases presented systemic pathologies. All cases presented with a unilateral suprachoroidal hemorrhage. Only 2/8 patients had ocular comorbidities. Complications requiring treatment were noted in 4/8 cases, including 2 cases that resulted in the loss of the vision following an acute angle-closure glaucoma. Spontaneous resolution of the hemorrhage was observed in the other 4 patients. In 6/8 cases, vision recovered over a mean period of 10 weeks. In conclusion, spontaneous suprachoroidal hemorrhage following a Valsalva maneuver in eyes with no history of ocular surgery or trauma is rare, and has been associated with advanced age, cardiovascular disease and asthma. In severe cases (2/8) the eye was lost, while most cases (6/8) recovered, presenting a good visual outcome.
Keywords: suprachoroidal hemorrhage; spontaneous; Valsalva maneuver